Remoción de fosfato de ambientes acuáticos utilizando nanopartículas modificadas de Fe-Co/Quitosan - Issaian, Tadeh; Reyes Cuellar, Julia Costanza (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Chitosan modified iron-cobalt nanoparticles (CMNPs) were used for phosphate adsorption in synthetic wastewater and river water from the Jordan river in Tunja, Boyacá, Colombia. Phosphate adsorption by CMNPs reached 52.7% in synthetic wastewater and 58.7% in water taken from the Jordan river. This indicates that the CMNPs ability to adsorb phosphates is independent of other components within river water. Additionally, adsorption measurements were taken using the average pH, temperature, and phosphate concentration of the river water in order to ensure results comparable to those of (Kim 2017). A maximum adsorption rate of 0.138 mg of phosphate per gram of adsorbent was found with the majority of adsorption taking place within the first 15 minutes of contact with the adsorbent. The adsorption of phosphates using CMNPs presents an effective and environmentally friendly solution to reducing phosphates in aquatic ecosystems without altering the characteristics of river water.